Overexpression of the transporters AtZIP1 and AtMTP1 in cassava changes zinc accumulation and partitioning - Gaitán-Solís, Eliana; Taylor, Nigel J.; Siritunga, Dimuth; Stevens, William; Schachtman, Daniel P. (Frontiers in Plant Science, 2015)
Zinc deficiency in humans is a serious problem worldwide with an estimated one third of populations at risk for insufficient zinc in diet which leads to impairment of cognitive abilities and immune system function. The goal of this research was to increase the bioavailable zinc in the edible portion of cassava roots to improve the overall zinc nutrition of populations that rely on cassava as a dietary staple. To increase zinc concentrations, two A. thaliana genes coding for ZIP1 and MTP1 were overexpressed with a tuber-specific or constitutive promoter. Eighteen transgenic events from four constructs, out of a total of 73 events generated, showed significantly higher zinc concentrations in the edible portion of the storage root compared to the non-transgenic controls. The zinc content in the transgenic lines ranged from 4 - 73 mg/Kg Dry Weight (DW) as compared to the non-transgenic control which contained 8 mg/Kg. Striking changes in whole plant phenotype such as smaller plant size and chlorotic leaves were observed in transgenic lines that over accumulated zinc. In a confined field trial five transgenic events grown for 12 months showed a range of zinc concentrations from 18 – 217 mg/Kg DW. Although the overexpression of zinc transporters was successful in increasing the zinc concentrations in 25% of the transgenic lines generated, it also resulted in a decrease in plant and tuber size and overall yield due to what appears to be zinc deficiency in the aerial parts of the plant.